Integrated Marketing Communicationi: Advertisements on Children and Women Body and Ethical Value Perception - YAZGAN, AYŞE MÜGE (My University, 2024)
The concepts of ethics and morality are closely related to each other. Both consist of ideals and virtues, aim to reduce harm and evil. However, morality is different from ethics since it is changeable. It varies according to mentalities. Ethics is universal and a fundamental part of moral values. The purpose of this study is to analyze ethical violations in integrated marketing communications. In the research, descriptive analysis made by observation method was experienced on randomly selected advertisements using children's and women's bodies. Answers were sought to the questions of how an advertisement can be ethical. According to the results obtained, the ethical relations of advertisements on national and international platforms were revealed through teleological and deontological theories. Compliance with ethical principles makes society members dynamic, optimistic, and motivated. This situation increases the living standard of the society. It is considered that this research will contribute to the field as it examines violations of ethical principles through advertisements and makes suggestions. Keywords: Ethics; Teleological ethics; Deontological ethics; Integrated marketing communication; Commercials; Social responsibilities

Etik ve ahlak kavramları birbiriyle yakından ilişkilidir. İdeallerden ve erdemlerden oluşmaktadır, zararı ve kötülüğü azaltmayı amaçlamaktadır. Ahlak değişkendir. Zihniyetlere göre değişir. Etik evrenseldir ve ahlaki değerlerin temel bir parçasıdır. Bu çalışmanın amacı bütünleşik pazarlama iletişimindeki etik ihlalleri analiz etmektir. Araştırmada çocuklar ve kadın vücudu kullanılmış reklamlar üzerinde gözlem metodu ile betimsel analiz yapılmıştır. Bir reklamın nasıl etik olabileceği sorularına yanıt aranmıştır. Elde edilen sonuçlara göre, ulusal ve uluslararası platformdaki reklamların teleolojik ve deontolojik teoriler üzerinden etik ilişkileri ortaya konulmuştur. Etik ilkelere uyum toplum üyelerini dinamik, iyimser kılmakta ve motive etmektedir. Bu durum toplumun yaşam standardını yükseltmektedir. Yapılan araştırmanın alana katkı sağlayacağı düşünülmektedir. Anahtar Kelimeler: Etik; Teleolojik etik; Deontolojik etik; Bütünleşik pazarlama iletişimi; Reklamlar; Sosyal sorumluluklar
Bütünleşik Pazarlama İletişimi: Çocuklar ve Kadın Vücudu üzerine Reklamlar ve Etik Değer Algısı
Keywords: Etik; Teleolojik etik; Deontolojik etik; Bütünleşik pazarlama iletişimi; Reklamlar; Sosyal sorumluluklar; Ethics; Teleological ethics; Deontological ethics; Integrated marketing communication; Commercials; Social responsibilities